Gender Differences in Age-Related Changes in Cardiac Autonomic Nervous Function - Shailaja Moodithaya; Sandhya T. Avadhany (Journal of Aging Research)
Ageing is associated with changes in cardiac autonomic control as measured by Heart Rate Variability (HRV). Not many studies have explored the influence of gender on age-related changes in cardiac autonomic regulation. This study evaluated the gender differences in age-associated changes in cardiac autonomic nervous activity by assessing HRV using frequency domain analysis of short-term stationary R-R intervals. HRV was studied in healthy males and females ranging in age from 6 to 55 years. Total power and absolute power in High-Frequency (HF) and Low-Frequency (LF) components as well as HF in normalized unit declined significantly with ageing. The HF/LF ratio was significantly higher in the adolescent and adult females compared to male of these age groups. This study suggests that gender differences exist in age-related changes in HRV. The finding that gender differences are limited to adolescent and adult age groups may indicate a role for female sex hormones in cardiac autonomic modulation.